Different Slopes for Different Folks: Self-Esteem Instability and Gender as Moderators of the Relationship between Self-Esteem and Attitudinal Aggression - Webster, G. (Institutional Knowledge at Singapore Management University, 2007)
The present research examined the relationships among self-esteem level, temporal self-esteem instability, gender, and self-reported aggression. Self-esteem level was negatively related to attitudinal aggression, although this relationship varied as a joint function of self-esteem instability and gender. It was strongest among men with unstable self-esteem and among women with stable self-esteem. Although self-esteem instability and narcissism (Study 3) were each positively related to behavioral aggression, the relationship between narcissism and attitudinal aggression varied as a function of self-esteem instability. The relationship between narcissism and attitudinal aggression was positive among people with stable self-esteem, but negative among people with unstable self-esteem, regardless of gender. The importance of considering gender, self-esteem instability, and narcissism in the self-esteem/aggression debate is discussed.